Multiwavelength behaviour of the blazar 3C 279: decade-long study from γ-ray to radio. Issue 3 (11th January 2020) - Larionov, V M; Jorstad, S G; Marscher, A P; Villata, M; Raiteri, C M; Smith, P S; Agudo, I; Savchenko, S S; Morozova, D A; Acosta-Pulido, J A; Aller, M F; Aller, H D; et al.
ABSTRACT: We report the results of decade-long (2008–2018) γ-ray to 1 GHz radio monitoring of the blazar 3C 279, including GASP/WEBT, Fermi and Swift data, as well as polarimetric and spectroscopic data. The X-ray and γ-ray light curves correlate well, with no delay $\gtrsim 3$ h, implying general cospatiality of the emission regions. The γ-ray–optical flux–flux relation changes with activity state, ranging from a linear to a more complex dependence. The behaviour of the Stokes parameters at optical and radio wavelengths, including 43 GHz Very Long Baseline Array images, supports either a predominantly helical magnetic field or motion of the radiating plasma along a spiral path. Apparent speeds of emission knots range from 10 to 37c, with the highest values requiring bulk Lorentz factors close to those needed to explain γ-ray variability on very short time-scales. The Mg ii emission line flux in the 'blue' and 'red' wings correlates with the optical synchrotron continuum flux density, possibly providing a variable source of seed photons for inverse Compton scattering. In the radio bands, we find progressive delays of the most prominent light-curve maxima with decreasing frequency, as expected from the frequency dependence of the τ = 1 surface of synchrotron self-absorption. The global maximum in the 86 GHz light curve becomes less prominent at lower frequencies, while a local maximum, appearing in 2014, strengthens toward decreasing frequencies, becoming pronounced at ∼5 GHz. These tendencies suggest different Doppler boosting of stratified radio-emitting zones in the jet.